The shrinkage behavior of boreholes drilled through deepwater creeping salt formations in West Africa - Wang, Mingchun; Deng, Jingen; Li, Zhong; Li, Mengbo; Xing, Zixiao; Zhang, Zhe; Yan, Chuanliang (Frontiers in Energy Research, 2024)
Introduction: Salt formations are complex and pose significant risks during oil and gas drilling. Creep behavior in salt formations under geostress can jeopardize drilling safety. Methods: This study analyzes the shrinkage behavior of boreholes drilled through salt formations in West Africa’s Block B, with emphasis on the differential creep rates in two horizontal principal stress directions and the evolution of wellbore shape over time. The impact of drilling fluid density on shrinkage rates is also investigated. Results: After drilling through salt formations, the creep rates differ between the two horizontal principal stress directions. Shrinkage is faster in the direction of minimum horizontal principal stress and slower in the direction of maximum horizontal principal stress. Over time, shrinkage rates converge, resulting in a transition from elliptical to circular wellbore shape. Higher drilling fluid density leads to reduced shrinkage rates. Discussion: These findings contribute to the theoretical guidance for drilling fluid density selection in salt formations.